Feed additives for swine: Fact sheets – acidifiers and antibiotics - Jacela, J.Y.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Renter, David G.; Dritz, Steven S. (My University, 2013)
Feed additives are non-nutritive products used in swine diets to improve production efficiency and performance. If chosen carefully and used properly, feed additives can be effective and can help increase the profi tability of pig production. Not all feed additives are the same or provide a benefi cial response and, therefore, choosing a product will depend on the farm’s specific situation and needs. This series of fact sheets includes some of the major classifications of products used as feed additives. Every effort has been made to ensure that all the information in every fact sheet is current and based on the latest scientific publications available at the time of writing. The objective of these fact sheets is to discuss some of the basic concepts to help producers improve their understanding of these products. They also aim to promote more responsible and judicious use of feed additives. Feed-additive products used in swine diets include natural and synthetic substances and have been grouped in this series of fact sheets according to the classifications shown in the text box. Each group of feed additives is discussed in a separate fact sheet, with special emphasis on some of the common questions that producers might have for each product. Feed additives offer a variety of potential benefits. However, they add to total production cost and should be evaluated carefully. Because their use in pig diets is to improve performance and profitability, an effective feed-additive product must be able to pay for itself. It must be able to provide an improvement in productivity that is, at minimum, equivalent to the added cost of the feed-additive product. This highlights the value of scientifi c data from well-designed experiments as the basis for evaluating such products. Having access to such information is critical in determining if one product’s claims are actually possible and repeatable in commercial settings. Producers must always try to verify that the data for a particular product came from controlled, unbiased experiments with supporting statistical data. When choosing between feed-additive products, priority for using a specific product should be given to those that have been shown to provide consistent results in research trials.
Keywords: Swine; Acidifiers; Feed Additives; Antibiotics; Growth